2008
DOI: 10.1590/s0066-782x2008000500006
|View full text |Cite
|
Sign up to set email alerts
|

Acompanhamento a longo prazo de pacientes com indicação de desfibrilador implantável como prevenção primária de morte súbita

Abstract: SummaryBackground: Recent MADIT II and SCD-HeFT trials have led to an expansion of indications for use of prophylactic Implantable Cardioverter Defibrillator (ICD) in patients with severe left-ventricular impairment. This therapy has not been fully adopted in our health care system, mainly due to its high cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In another study, in fact, subgroup analysis of data from 459 patients randomly assigned to standard therapy or standard therapy plus an ICD revealed that LVEF ≥20%, male gender, and NYHA Class III but not Class I or II, were significantly associated with improved survival [13]. A Brazilian study compared 102 patients who did not receive an ICD to patients in the placebo arm of another major primary prevention study, SCD-HeFT, and found that the mortality rates were similar between the 2 groups, causing them to conclude that their patients were similar, and may benefit from ICD therapy if economic constraints could be removed [14]. Likewise, our patients shared several similarities with the RCT patients; for example age, gender, proportion of patients with ischemic cardiomyopathy, and distribution among NYHA functional classes was similar to those in the 12 RCTs included in the systematic review by Ezekowitz et al [4].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, in fact, subgroup analysis of data from 459 patients randomly assigned to standard therapy or standard therapy plus an ICD revealed that LVEF ≥20%, male gender, and NYHA Class III but not Class I or II, were significantly associated with improved survival [13]. A Brazilian study compared 102 patients who did not receive an ICD to patients in the placebo arm of another major primary prevention study, SCD-HeFT, and found that the mortality rates were similar between the 2 groups, causing them to conclude that their patients were similar, and may benefit from ICD therapy if economic constraints could be removed [14]. Likewise, our patients shared several similarities with the RCT patients; for example age, gender, proportion of patients with ischemic cardiomyopathy, and distribution among NYHA functional classes was similar to those in the 12 RCTs included in the systematic review by Ezekowitz et al [4].…”
Section: Discussionmentioning
confidence: 99%